2014
DOI: 10.1016/j.neuron.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Activity Patterns Carry Information about Objects in Temporal Context

Abstract: SUMMARY The hippocampus is critical for human episodic memory, but its role remains controversial. One fundamental question concerns whether the hippocampus represents specific objects or assigns context-dependent representations to objects. Here, we used multivoxel pattern similarity analysis of fMRI data during retrieval of learned object sequences to systematically investigate hippocampal coding of object and temporal context information. Hippocampal activity patterns carried information about the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
383
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(452 citation statements)
references
References 87 publications
50
383
9
1
Order By: Relevance
“…We propose that time intervals became an implicit temporal associate to the cue-target pairs in associative memory. The cue-based retrieval of the temporal memory trace in turn guided attentional allocation to optimize recognition of the probe as the target item, similarly to how stimulus processing for nontarget items is optimized when it is associated in memory to the target item (Moores et al 2003).Recent studies showed hippocampal involvement in the temporal organization of discontinuous events during memory encoding and retrieval (Staresina and Davachi 2009;Schapiro et al 2012;Hsieh et al 2014). We predict that brain activity related to the implicit memory trace of time in the TPAT also includes the hippocampus.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We propose that time intervals became an implicit temporal associate to the cue-target pairs in associative memory. The cue-based retrieval of the temporal memory trace in turn guided attentional allocation to optimize recognition of the probe as the target item, similarly to how stimulus processing for nontarget items is optimized when it is associated in memory to the target item (Moores et al 2003).Recent studies showed hippocampal involvement in the temporal organization of discontinuous events during memory encoding and retrieval (Staresina and Davachi 2009;Schapiro et al 2012;Hsieh et al 2014). We predict that brain activity related to the implicit memory trace of time in the TPAT also includes the hippocampus.…”
mentioning
confidence: 86%
“…Previous studies showed that temporal order of discontinuous events (Tubridy and Davachi 2011;Hsieh et al 2014) and temporal proximity between events (Schwartz et al 2005;Schapiro et al 2012) facilitate memory formation and retrieval. We extend these findings by showing that cue-dependent memory of elapsed time also facilitates retrieval of associated visual objects.…”
mentioning
confidence: 99%
“…Oppenheim, et al, 2010). Of note, both the DLPFC and hippocampus have been implicated consistently in a working memory circuit, especially for item order information (Hsieh, et al, 2011;Hsieh, et al, 2014;Marshuetz, 2005). It is therefore interesting that this minimal working memory circuit was the only significant finding in our fMRI experiment.…”
Section: The Role Of Working Memory In the Semantic Interference Effementioning
confidence: 64%
“…Hippocampal lesions have been shown to impair performance on short-term retention tasks, with the hippocampus playing an important role in working memory more generally (for reviews, see Jonides et al, 2008;Marshuetz, 2005;Ranganath & Blumenfeld, 2005). Of note, both the DLPFC and hippocampus have been implicated consistently in a working memory circuit, especially for item order information (Hsieh, et al, 2011;Hsieh, et al, 2014;Marshuetz, 2005). This network would be consistent with Crowther and Martin's (2014) suggestion that working memory encodes and then tracks items within-cycles, permitting the participant to predict which pictures will appear on subsequent trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation